RADIOLOGICAL APPROACH TO NEPHROBLASTOMA IN CHILDHOOD - Memeti-Tefiku, Advie; Dimitrijevikj, Kristina (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Abstract Nephroblastoma (Wilms’ tumor) is the most common malignant kidney tumor in children, and the bilateral form occurs in approximately 5–10% of cases. It is an undifferentiated mesodermal tumor, containing a variable amount of embryonic renal elements (blastema, epithelium, and stroma). In this paper, we present a case of a 4-year-old child with bilateral nephroblastoma, who underwent right-sided nephrectomy due to a dominant tumor mass and adjuvant chemotherapy according to the SIOP protocol. After completion of treatment, significant radiological and clinical regression of lesions in the remaining kidney was recorded. During the follow-up of several months after the end of therapy, no signs of relapse or new progression of the disease were observed. The case emphasizes the importance of multimodal treatment and careful monitoring in patients with bilateral nephroblastoma with special emphasis on the current key role that imaging plays in preserving renal function and achieving a favorable outcome. Keywords: nephroblastoma, bilateral, nephrectomy, regression, relapses